Structural Mapping of the Bentong‐Raub Suture Zone Using PALSAR Remote Sensing Data, Peninsular Malaysia: Implications for Sediment‐hosted/Orogenic Gold Mineral Systems Exploration. Issue 4 (13th September 2016) - Pour, Amin Beiranvand; Hashim, Mazlan; Makoundi, Charles; Zaw, Khin
Abstract: The Bentong‐Raub Suture Zone (BRSZ) of Peninsular Malaysia is one of the major structural zones in Sundaland, Southeast Asia. It forms the boundary between the Gondwana‐derived Sibumasu terrane in the west and Sukhothai Arc in the east. The BRSZ is genetically related to the sediment‐hosted/orogenic gold deposits associated with the major lineaments in the Central Gold Belt of Peninsular Malaysia. In this investigation, the Phased Array type L‐band Synthetic Aperture Radar (PALSAR) satellite remote sensing data were used to map major geological structures in Peninsular Malaysia and provide detailed characterization of lineaments and curvilinear structures in the BRSZ, as well as their implication for sediment‐hosted/orogenic gold exploration in tropical environments. Major structural lineaments such as the Bentong‐Raub Suture Zone (BRSZ) and Lebir Fault Zone, ductile deformation related to crustal shortening, brittle disjunctive structures (faults and fractures) and collisional mountain range (Main Range granites) were detected and mapped at regional scale using PALSAR ScanSAR data. The major geological structure directions of the BRSZ were N–S, NNE–SSW, NE–SW and NW–SE, which derived from directional filtering analysis to PALSAR fine and polarimetric data. The pervasive array of N–S faults in the Central Gold Belt and surrounding terrain is mainly linked to the N–S trending of the Suture Zone. N–S striking lineaments are often cut by younger NE–SW and NW–SE‐trending lineaments. Gold mineralized trend lineaments are associated with the intersection of N–S, NE–SW, NNW–SSE and ESE–WNW faults and curvilinear features in shearing and alteration zones. Compressional tectonic structures such as the NW–SE trending thrust, ENE–WSW oriented faults in mylonite and phyllite, recumbent folds and asymmetric anticlines in argillite are high potential zones for gold prospecting in the Central Gold Belt. Three generations of folding events in Peninsular Malaysia have been recognized from remote sensing structural interpretation. Consequently, PALSAR satellite remote sensing data is a useful tool for mapping major geological structural features and detailed structural analysis of fault systems and deformation areas with high potential for sediment‐hosted/orogenic gold deposits and polymetallic vein‐type mineralization along margins of Precambrian blocks, especially for inaccessible regions in tropical environments. Abstract : The Phased Array type L‐band Synthetic Aperture Radar (PALSAR) satellite remote sensing data were used to map major geological structures in Peninsular Malaysia and provide detailed characterization of lineaments and curvilinear in the BRSZ, as well as its implication for sediment‐hosted/orogenic gold exploration in tropical environments.